2017
DOI: 10.1371/journal.pone.0177318
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of respiratory muscle strength and activity in Myotonic dystrophy

Abstract: ObjectiveTo evaluate sensitivity/specificity of the maximum relaxation rate (MRR) of inspiratory muscles, amplitude of electromyographic activity of the sternocleidomastoid (SCM), scalene (SCA), parasternal (2ndIS) and rectus abdominis (RA) muscles; lung function and respiratory muscle strength in subjects with Myotonic dystrophy type 1 (DM1) compared with healthy subjects.Design and methodsQuasi-experimental observational study with control group. MRR of inspiratory muscles, lung function and amplitude of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…In our study, all parameters derived from the SNIP curve were significantly different between middle stage ALS and healthy subjects, being in agreement with two previous studies performed in subjects with neuromuscular disorders (47,49). Evangelista et al (49), observed that a reduced MRR was reliable in identifying the delayed relaxation of the respiratory muscles in myotonic dystrophy type 1 patients when compared to healthy controls; while Garcia-Rio et al (47), despite heterogeneity of the study population, found that the decreased MRR of neuromuscular disease patients was accompanied by the deterioration in the functional reserve of the diaphragm as well as of the inspiratory muscles. The rationale for measuring relaxation rates from pressure curves is based on the assumption that the decay portion of the curve, when expiration is totally passive, corresponds to the relaxation phase of inspiratory muscle contraction (18).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, all parameters derived from the SNIP curve were significantly different between middle stage ALS and healthy subjects, being in agreement with two previous studies performed in subjects with neuromuscular disorders (47,49). Evangelista et al (49), observed that a reduced MRR was reliable in identifying the delayed relaxation of the respiratory muscles in myotonic dystrophy type 1 patients when compared to healthy controls; while Garcia-Rio et al (47), despite heterogeneity of the study population, found that the decreased MRR of neuromuscular disease patients was accompanied by the deterioration in the functional reserve of the diaphragm as well as of the inspiratory muscles. The rationale for measuring relaxation rates from pressure curves is based on the assumption that the decay portion of the curve, when expiration is totally passive, corresponds to the relaxation phase of inspiratory muscle contraction (18).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, measurements of nasal sniffs are simple, tolerated, and minimally invasive and can provide a quantitative response index to fatigue and therapeutic interventions in neuromuscular disease patients ( 47 , 48 ). In our study, all parameters derived from the SNIP curve were significantly different between middle stage ALS and healthy subjects, being in agreement with two previous studies performed in subjects with neuromuscular disorders ( 47 , 49 ). Evangelista et al ( 49 ), observed that a reduced MRR was reliable in identifying the delayed relaxation of the respiratory muscles in myotonic dystrophy type 1 patients when compared to healthy controls; while Garcia-Rio et al ( 47 ), despite heterogeneity of the study population, found that the decreased MRR of neuromuscular disease patients was accompanied by the deterioration in the functional reserve of the diaphragm as well as of the inspiratory muscles.…”
Section: Discussionsupporting
confidence: 93%
“…Myotonic dystrophy type 1 (DM1) is an autosomal dominant neuromuscular disorder and is the most common form of muscular dystrophy in adults . While DM1 is a multi‐systemic disorder significantly affecting cardiac muscle, brain and other tissues, a primary cause of mortality is due to skeletal muscle weakness and wasting of respiratory muscles . Weakness typically begins in distal muscles, leading to impaired ambulation, and difficulty with fine motor tasks and is a top concern among individuals affected by DM1 .…”
Section: Introductionmentioning
confidence: 99%